Extended Bonner sphere spectrometer for dynamic neutron spectrum on HL-2A - 蒋春雨 曹靖 刘子豪 蒋小菲 宋先瑛 张轶泼 阴泽杰 (Plasma science & technology, 2017)
The extended Bonner sphere spectrometer （EBSS） at the HL-2A tokamak for the neutron spectrum is described. This device was developed on the basis of previous Bonner sphere spectrometry （BSS）, aiming to obtain a more accurate neutron spectrum in the HL-2A tokamak hall. The previous BSS contained eight Bonner spheres （BS）. This EBSS contains 13 3He-filled detectors embedded in polyethylene spheres （PS）, pre-amplifiers, and a parallel processing data acquisition system （DAQ）. A response matrix is simulated in Geant4 taking the effect of the environment into account.